ELECTRONIC DICTIONARY OF SPORTS METAPHORS AS AN INSTRUMENT TO DEVELOP THE UKRAINIAN COMPUTER LEXICOGRAPHY - Karabuta, Olena; Mandych, Tamara; Lemeshchuk, Oleksandr (Journal of Information Technologies in Education (ITE), 2020)
The article partially considers the issue of Ukrainian computer lexicography, the development of which requires constant updating and application of new approaches. At the current stage, linguists, as well as experts in the field of philology and journalism, use electronic texts and Internet resources for work and analysis significantly more frequent, rather than traditional printed sources. For fast and high-quality processing of a large array of language units, it is necessary to find tools that would provide both a convenient keyword search in the database and the ability to perform professional analysis of language units «online» according to certain criteria. The proposed study highlights the main directions of development of electronic lexicographic resources on the Internet related to work with various aspects of the Ukrainian language (word interpretation, translation, spelling, word change, etc.) and describes the main advantages and disadvantages of already created dictionaries. The functional possibilities of lexicographical sources of philological orientation available in the «online» mode are analyzed. A few sports dictionaries posted on the Internet, which are closely related to the topic of our study, are considered separately. The authors present the experience of developing a dictionary of sports metaphors, structured in 4 categories: anthropomorphic, sociomorphic, artifact and natural morphological types, within which a system of metaphorical models is built. The dictionary is designed using the MediaWiki mechanism, the parameters of which meet the needs of users and facilitate the maintenance and administration of the site. Systematization of language units and their search on the created site provides alphabetical and categorical principles. The developed prototype of the electronic dictionary is one of the tools for teaching students of philology and journalism, a platform for conducting their own research, as well as a segment of the Ukrainian media space that can meet the probable search queries of users.